معوقات تسجيل المقررات الدراسية في ضوء عدد الساعات والتخصص الدراسي من وجهة نظر طالبات كلية التربية الأساسية بالكويت - العجمي، حمد بليه; عباس، زينب عبدالرضا (جامعة الأزهر - كلية التربية, 2024)
هدف البحث الكشف عن معوقات تسجيل المقررات الدراسية في ضوء عدد الساعات والتخصص الدراسي من وجهة نظر طالبات كلية التربية الأساسية، وقد اتبع البحث المنهج الوصفي، واعتمد على الاستبانة في جمع البيانات بعنوان (استبانة معوقات التسجيل للمقررات الدراسية)، وطبق على عينة وبلغت عينة البحث ۳۸۳ طالبة، واستخدم البحث الأساليب الإحصائية التالية: بعض مقاييس النزعة المركزية، معامل ارتباط بيرسون، النسبة المئوية، تحليل التباين في اتجاه واحد (ANOVA)، اختبار أقل فرق دال إحصائيا (LSD)، وتوصل البحث إلى عدة نتائج كان من أهمها: أن من أهم المعوقات التي تواجه طالبات كلية التربية الأساسية في عملية تسجيل المقررات الدراسية ما يلي: مشكلات نظام التسجيل الإلكتروني سبب في توقف التسجيل، المحسوبية (الواسطة) تسجل طلبة غير مستحقين مما يغلق الشعب مبكرا، تحديد أوقات التسجيل الإلكتروني أثناء المحاضرات فوت على فرص التسجيل المبكر، قلة عدد الشعب المتاحة للتسجيل تسبب في تأخر تخرجي، ضعف تفاعل الإرشاد الأكاديمي في الأقسام العلمية، وبالنسبة للفروق بين الطالبات وفقا لعدد الساعات المسجلة، فقد كانت لصالح المجموعات التالية: (أقل من ٦٠ ساعة) و(أقل من ٩٠ ساعة) و(أكثر من ٩٠ ساعة) على حساب مجموعة (أقل من ٣٠ ساعة) بشكل دال إحصائيا، وبالنسبة للفروق بين الطالبات وفقا للتخصص الدراسي فقد كانت لصالح طلبة (التخصصات الأدبية) على حساب مجموعتي (التخصصات العلمية والتخصصات النوعية) بشكل دال إحصائيا. The research aimed to reveal the obstacles to registering academic courses in light of the number of hours and academic specialization from the point of view of female students in the College of Basic Education. The research followed the descriptive approach and relied on a questionnaire in collecting data entitled (Questionnaire of obstacles to registering for academic courses), and it was applied to a sample of 383 female students. The research used the following statistical methods: some measures of central tendency, Pearson correlation coefficient, percentage, one-way analysis of variance (ANOVA), least statistically significant difference (LSD) test. The research reached several results, the most important of which were: that one of the most important obstacles that In the process of registering courses, female students of the College of Basic Education face the following: problems with the electronic registration system that cause registration to stop, nepotism (nepotism) registers undeserving students, which closes classes early, setting times for electronic registration during lectures that make me miss opportunities for early registration, small number of classes. Available for registration caused the delay in my graduation, weak interaction of academic guidance in the scientific departments, and as for the differences between the female students according to the number of registered hours, they were in favor of the following groups: (less than 60 hours), (less than 90 hours), and (more than 90 hours). At the expense of the group (less than 30 hours) in a statistically significant way, and as for the differences between the female students according to academic specialization, they were in favor of the students (literary specializations) at the expense of the two groups (scientific specializations and qualitative specializations) in a statistically significant way.
Keywords: نظام التسجيل الإلكتروني -- المناهج الدراسية -- التخصصات الجامعية -- كلية التربية الأساسية -- طلبة الجامعات